Integral Formulaeas Involving Two H I-function and Multivariable Polynomials (Global Journal of Science Frontier Research, 2012)
The aim of the present paper is to derive a new Integral formulae's for the H -function due to Inayat-Hussain whose based upon some integral formulae due to Qureshi et.al. The results are obtained in a compact form containing the multivariable Polynomials.
Keywords: general class of polynomials; generalized wright hypergeometric function; H-function; generalized wright hypergeometric function.